2004
DOI: 10.1128/mcb.24.15.6763-6772.2004
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Nitrogen Species-Induced Cell Death Requires Fas-Dependent Activation of c-Jun N-Terminal Kinase

Abstract: Nitrogen dioxide is a highly toxic reactive nitrogen species (RNS) recently discovered as an inflammatory oxidant with great potential to damage tissues. We demonstrate here that cell death by RNS was caused by c-Jun N-terminal kinase (JNK). Activation of JNK by RNS was density dependent and caused mitochondrial depolarization and nuclear condensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 70 publications
(88 reference statements)
1
38
0
Order By: Relevance
“…However, a number of drugs and agents are able to activate a multiprotein complex that promotes the formation of a large channel in the IM, the so-called permeability transition pore (PTP). 25,42,[48][49][50] Changes in mitochondrial membrane potential-∆Ψ m -the energy source of oxphos-are often observed in apoptotic cells and are interpreted to derive from the PTP opening. However, most frequently these changes occur after the initial loss of OM permeability, thereby reflecting a mixture of caspase-mediated and caspase-independent damages, including the opening of the PTP.…”
Section: The Mitochondrial Pathway Of Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of drugs and agents are able to activate a multiprotein complex that promotes the formation of a large channel in the IM, the so-called permeability transition pore (PTP). 25,42,[48][49][50] Changes in mitochondrial membrane potential-∆Ψ m -the energy source of oxphos-are often observed in apoptotic cells and are interpreted to derive from the PTP opening. However, most frequently these changes occur after the initial loss of OM permeability, thereby reflecting a mixture of caspase-mediated and caspase-independent damages, including the opening of the PTP.…”
Section: The Mitochondrial Pathway Of Apoptosismentioning
confidence: 99%
“…25,[44][45][46][47] Oxidative phosphorylation (oxphos) takes place within the IM. 25,48,49 Because of the crucial importance of oxphos in producing cellular ATP, which is also essential for apoptosis signaling (apoptosome formation, see below), genuine apoptotic stimuli normally do not affect the properties of the IM. However, a number of drugs and agents are able to activate a multiprotein complex that promotes the formation of a large channel in the IM, the so-called permeability transition pore (PTP).…”
Section: The Mitochondrial Pathway Of Apoptosismentioning
confidence: 99%
“…It has been reported that PARP-1 hyperactivation prompts mitochondria dysfunction, which in turn releases apoptosis-inducing factor (AIF) from the mitochondria to the nucleus (29,30). The involvement of c-Jun N-terminal kinase has recently been demonstrated in caspaseindependent cell death by several groups of investigators (31)(32)(33). Receptor-interacting protein 1 (RIP1) and TNF receptorassociated factor 2 (TRAF2) are known to play important roles in cellular responses to TNF and TNF family members, and both were shown to be required for TNF-induced caspase-independent cell death (24,34).…”
mentioning
confidence: 99%
“…Two MAPKKK (MEKK1 and ASK1) and one MAPKK (MKK4) have been implicated in RNS-induced JNK activation. 7,29,30 However, little is known about the signaling mechanism upstream of MAPKKK in RNS-mediated JNK activation. In this study, we provide unequivocal evidence showing the critical role of TRAF2 upstream of ASK1 in RNS-mediated JNK activation.…”
Section: Discussionmentioning
confidence: 99%